A study on compositional characteristics of pumpkin based reconstituted Kheer - Shaikh, Adil; Changade, Sudhakar P; Dhotre, Anant V; Datir, Rupesh P (Indian Journal of Dairy Science, 2017)
Present study investigated the effect of incorporation of pumpkin powder in dry kheer mix onthe compositional characteristics of reconstituted kheer obtained therefrom. The pumpkin powder was incorporated in dry kheer mix at the rate of 1 %, 2 %, 3 % and 4 %. Equal quantity of Skim Milk Powder (SMP) was reduced from the mix to maintain concentration of other constituent’s i.e. sugar (36 %), rice (10 %), hydrogenated fat (7 %), nutmeats (2.1 %), cardamom (0.7 %) and color (0.2 %) weight by weight. Kheer reconstituted from the mix was compared with the kheer prepared by addition of pumpkin flesh into milk followed by concentration to25 %, which was taken as control. The product was analyzed for moisture, fat, protein, acidity, reducing sugar, total sugar and ash. Results revealed that increased level of pumpkin powder leads to significant decrease in moisture and protein contents. But the change in fat, reducing sugar, total sugar content and lactic acidity was non-significant at 5 % level of significance.